Stomaplasty with pannicuectomy in an obese patient with stomal retraction: A case report. (2016) - Ito, Eisaku; Kosaka, Masaaki; Kawaguchi, Chie; Yoshida, Masashi; Ohdaira, Hironori; Nakashima, Keigo; Suzuki, Norihiko; Imakita, Tomonori; Tsutsui, Nobuhiro; Kitajima, Masaki; Suzuki, Yutaka
Highlights: Stomal retraction is a common complication of stomas and results in poor fitting, frequent leakage, and peristomal dermatologic problems. Treatment of stomal retraction typically involves an intraperitoneal stoma revision. Stomaplasty with pannicuectomy is a feasible option in obese patients with stomal retraction. Abstract: Introduction: Stomal retraction is a common complication following stoma formation. A repeat surgical procedure for stomal revision is an invasive treatment that is often required as a result. Case presentation: An 81-year-old woman with obstructive rectal carcinoma and perforative peritonitis underwent an emergent anterior resection and colostomy (Hartmann's operation). After the operation, the patient changed the stoma pouch every day because of stomal retraction and leakage. Thirty-eight days after the operation, we performed a stomaplasty with pannicuectomy. Following this procedure, the patient changed the stoma pouch twice weekly. Discussion: Stomal retraction is caused by the thick subcutaneous fat and abnormal skin folds in obese patients, as well as the excess tension that is the result of inadequate mobilization. Treatment of stomal retraction typically requires an intraperitoneal stoma revision. Our method of panniculectomy with skin excision but without stomal revision does not involve an incision around the stoma and there is no risk of fecal contamination. Conclusion: We report a case of an obese patient who underwent stomaplasty with pannicuectomy for stomal retraction. We believe that stomaplasty with pannicuectomy is a feasible option in obese patients with stomal retraction.